Floodplain Forest Soil Nematode Communities as Influenced by Non-Native Acer negundo L. Invasion - Marek Renčo; Andrea Čerevková; Erika Gömöryová (Diversity, 2025)
Invasive plants can significantly alter the composition and functioning of soil ecosystems, which in turn affects soil fauna such as microorganisms; mesofauna including mites, springtails, nematodes, and insects; and other invertebrates. We used clusters of three different tree species to investigate how they affect the composition of belowground soil nematode communities. The clusters included Acer negundo (L.) (an invasive, non-native species), Fraxinus excelsior (L.), and Alnus glutinosa (Gaertn.) (both as native representatives) in floodplain forest habitats of the Morava River. We investigated the families, genera, trophic groups, and functional guilds of soil nematodes in each tree cluster to assess the usefulness of nematodes as indicators of the impact of alien tree species on native communities. The study was complemented by measuring basic soil physico-chemical properties. The data show that nematode communities were not sensitive to A. negundo invasion, as clusters of invasive trees had similar nematode abundance, genus richness, diversity, family and genus composition, and trophic structure compared to species-specific clusters of two native tree species. A cumulative total of 96 nematode genera, belonging to 52 families, were recorded in the investigated floodplain forest sites. The most abundant families across all clusters were Alaimidae, Cephalobidae, Hoplolaimidae, and Rhabditidae for all tree clusters. Among the genera, Helicotylenchus, Pratylenchus, Paratylenchus (as obligate plant parasites), Filenchus, and Malenchus (as facultative plant parasites), as well as Acrobeloides, Eucephalobus, Plectus, and Rhabditis (as bacterivores), were the most dominant taxa. The measured soil properties did not differ significantly among tree species (p < 0.05). Nevertheless, redundancy analysis identified a significant correlation between soil moisture content and abundance of several nematode genera, nematode trophic groups, and functional guilds. The results indicate that the presence of invasive ash-leaved maple trees in the studied floodplain forests had no adverse effect on the diversity and functional structure of soil nematode communities. This study offers initial insights into nematode communities in Acer negundo invaded habitats, but further studies are needed to verify these findings.